PENGARUH PEMBERIAN PUPUK KANDANG TERHADAP PERTUMBUHAN BIBIT ANGSANA (Pterocarpus indicus Willd) - Diyah Nur Fitriani; Gusti Muhammad Hatta; Muhammad Muchtar Effendy (Universitas Lambung Mangkurat, 2020)
The study was purpose to determine the effect of giving manure to the growth of angsana (Pterocarpus indicus Willd) seedlings, some growth parameters measured such as life percentage, height, increase in diameter and number of leaves. The study used a Completely Randomized Design (CRD) with 4 treatments and 10 replication. The results of the atudy showed that only the increase in diameter had a significant difference between the four growth parameters.Keywords: Influence; manure;diamter; pterocarpus indicus